'More than a day job, a fair job: music graduate employment in education'. (19th October 2020) - Brook, Scott; Comunian, Roberta; Jewell, Sarah; Lee, Jee Young
ABSTRACT: The focus on graduate employability for Creative Industries has tended to overlook the significance of the education sector as a destination. This article makes a case for the educational logic of music careers considered as an example of the developmental agenda embedded in the concept of 'culture'. It further supports this account by looking at longitudinal graduate destination data in both Australia and the UK that shows the importance of education employment to music careers. It considers music graduate outcomes in both countries according to university tier, graduate level employment, and career satisfaction. It finds that outcomes differ significantly in terms of gender, and that careers in education are no less rewarding than those in music professions. Attention to the 'educational logic of culture' suggests there are opportunities for creative industries policy to better support links between the creative economy and education.